2004
DOI: 10.1128/aem.70.11.6394-6400.2004
|View full text |Cite
|
Sign up to set email alerts
|

Air- and Dustborne Mycoflora in Houses Free of Water Damage and Fungal Growth

Abstract: Typically, studies on indoor fungal growth in buildings focus on structures with known or suspected water damage, moisture, and/or indoor fungal growth problems. Reference information on types of culturable fungi and total fungal levels are generally not available for buildings without these problems. This study assessed 50 detached single-family homes in metropolitan Atlanta, Ga., to establish a baseline of "normal and typical" types and concentrations of airborne and dustborne fungi in urban homes which were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
2
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(85 citation statements)
references
References 15 publications
6
74
2
3
Order By: Relevance
“…In addition, a study conducted in Greater New Haven, Connecticut revealed higher mean levels of culturable fungi (Ren et al, 1999) than found in the present study. However, the data collected in the Atlanta area and reported by Horner et al (2004) are close to our data with respect to the indoor median concentration of culturable fungi. This might be because (a) the climate conditions and vegetation in Atlanta are similar to those we observed in Cincinnati and (b) Horner et al pre-screened the sampling sites before measurement to focus on the houses free from water damage for minimizing the indoor sources of airborne fungi (similarly to our approach).…”
Section: Indoor and Outdoor Concentration Of Culturable Fungisupporting
confidence: 87%
“…In addition, a study conducted in Greater New Haven, Connecticut revealed higher mean levels of culturable fungi (Ren et al, 1999) than found in the present study. However, the data collected in the Atlanta area and reported by Horner et al (2004) are close to our data with respect to the indoor median concentration of culturable fungi. This might be because (a) the climate conditions and vegetation in Atlanta are similar to those we observed in Cincinnati and (b) Horner et al pre-screened the sampling sites before measurement to focus on the houses free from water damage for minimizing the indoor sources of airborne fungi (similarly to our approach).…”
Section: Indoor and Outdoor Concentration Of Culturable Fungisupporting
confidence: 87%
“…Many of the molds identified are allergenic, including Alternaria, Aspergillus, Cladosporium, Curvularia, and Penicillium (26). In general, the types of molds isolated after the storm were different from those previously reported for nonwaterdamaged buildings in the Southeastern United States (27).…”
Section: Mold Studies In New Orleans After Katrina and Ritacontrasting
confidence: 37%
“…Animal housings, water damped buildings, food processing plants, dumping sites etc. are various indoor and outdoor environments wherein higher concentration of bioaerosol have been associated with several health impacts indicating poor air quality (Eduard et al, 1993;Fischer et al, 2003;Horner et al, 2004;Shantha et al, 2009;Ghosh et al, 2015). Since airborne microorganisms mostly fall into respirable size range (with diameter < 10 µm), they usually have the capability to penetrate deep down into human lungs causing several health hazards (Reponen et al, 2001;Gorny and Dutkiewicz, 2002).…”
Section: Introductionmentioning
confidence: 99%